2016 10th International Symposium on Medical Information and Communication Technology (ISMICT) 2016
DOI: 10.1109/ismict.2016.7498891
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MRI compressed sensing image reconstruction with a graphics processing unit

Abstract: Compressed sensing (CS) magnetic resonance imaging (MRI) reconstruction reduces the scan time by undersampling the data but increases the image reconstruction time because a non-linear optimization problem must be iteratively solved to reconstruct the images. The growing demand for reducing the examination time in cardiac MRI led us to investigate opportunities to accelerate this non-linear optimization problem to facilitate the migration of CS into the clinical environment. Using 3D steady-state free precessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…To reduce the reconstruction time for CS, a graphics processor unit (GPU) implementation has also been evaluated. 22 A common LRM solver is a nuclear norm optimizer that uses a scheme such as iterative singular value thresholding. For CS/LRM, an iterative solver such as a conjugate gradient solver is generally used for evaluation of the data consistency of PI.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the reconstruction time for CS, a graphics processor unit (GPU) implementation has also been evaluated. 22 A common LRM solver is a nuclear norm optimizer that uses a scheme such as iterative singular value thresholding. For CS/LRM, an iterative solver such as a conjugate gradient solver is generally used for evaluation of the data consistency of PI.…”
Section: Discussionmentioning
confidence: 99%
“…Their experiments employed 3D steady-state free precession MRI images from five patients, and compared the speed and recon image quality on different parallel platforms, such as CPU, CPU with OpenMP, and GPU. Their recon results showed that the mean reconstruction time was 13.1±3.8 minutes on the CPU platform, 11.6±3.6 minutes on the CPU platform with OpenMP, and 2.5±0.3 minutes for the CPU platform with OpenMP plus GPU (40). And their image qualities estimated by image subtraction were very similar, which are comparable on different parallel architectures.…”
Section: Csmentioning
confidence: 93%
“…Because the NVIDIA CUDA library is more and more perfect to support for GPU computing, the complex sparse reconstruction methods are more easily implemented on GPUs without considering the hardware constrains on GPUs. Actually, there are recently some papers studying CS MR recon methods on GPU architectures (35)(36)(37)(38)(39)(40)(41)(42). For example, Zhuo et al presented a GPU-accelerated regularization reconstruction method with compensations for susceptibility-induced field inhomogeneity effects, which are incorporating a quadratic regularization term (35).…”
Section: Csmentioning
confidence: 99%
See 2 more Smart Citations